Exposure to coarse particulate matter during gestation and birth weight in the U.S. (September 2016) - Ebisu, Keita; Berman, Jesse D.; Bell, Michelle L.
Abstract: Few studies have explored the relationship between coarse particles (PM10-2.5 ) and adverse birth outcomes. We examined associations between gestational exposure of PM10-2.5 and birth weight. U.S. birth certificates data (1999–2007) were acquired for 8, 017, 865 births. Gestational and trimester exposures of PM10-2.5 were estimated using co-located PM10 and PM2.5 monitors≤ 35 km from the population-weighted centroid of mothers' residential counties. A linear regression model was applied, adjusted by potential confounders. As sensitivity analyses, we explored alternative PM10-2.5 estimations, adjustment for PM2.5, and stratification by regions. Gestational exposure to PM10-2.5 was associated with 6.6 g (95% Confidence Interval: 5.9, 7.2) lower birth weight per interquartile range increase (7.8 μg/m 3 ) in PM10-2.5 exposures. All three trimesters showed associations. Under different exposure methods for PM10-2.5, associations remained consistent but with different magnitudes. Results were robust after adjusting for PM2.5, and regional analyses showed associations in all four regions with larger estimates in the South. Our results suggest that PM10-2.5 is associated with birth weight in addition to PM2.5 . Regional heterogeneity may reflect differences in population, measurement error, region-specific emission pattern, or different chemical composition within PM10-2.5 . Most countries do not set health-based standards for PM10-2.5, but our findings indicate potentially important health effects of PM10-2.5 . Highlights: Only a few studies have explored birth outcomes in association with PM10-2.5 We explored associations between PM10-2.5 gestational exposure and birth weight. PM10-2.5 is associated with birth weight in addition to PM2.5. Our findings indicate potentially important health effects of PM10-2.5.